Decoupling Literacy and Verification: A Quantitative Study of Misinformation Resistance among Undergraduate Students - Kadek Devi Kalfika Anggria Wardani; Anak Agung Ngurah Eddy Supriyadinata Gorda; Steviona Abigael Lepong (Yayasan Nurul Yakin Bunga Tanjung, 2026)
The rapid spread of misinformation on social media has increased the importance of developing social media literacy as a core educational competency in higher education. This study examined the relationship between social media literacy and hoax-news prevention among undergraduate students and identified the specific competencies requiring instructional attention. A cross-sectional survey was conducted with 100 undergraduate students using a validated 27-item questionnaire measuring social media literacy and hoax-news prevention. Data were analyzed using descriptive statistics and simple linear regression after confirming instrument validity, reliability, and model assumptions. The findings revealed that students demonstrated a high overall level of social media literacy, which was positively and significantly associated with hoax-news prevention (p < .001). However, indicator-level analysis showed that source verification, particularly verifying the credibility of accounts before sharing information, was the weakest competency despite the high overall literacy score. These findings suggest that general social media literacy does not necessarily translate into effective misinformation verification behaviours. From an educational perspective, the results highlight the need to integrate structured instruction on critical evaluation and source verification into higher education curricula. Strengthening these competencies through teaching and learning activities may better prepare students to critically evaluate online information and reduce the spread of misinformation.